Cyberbullying: Review of an Old Problem Gone Viral - Aboujaoude, Elias; Savage, Matthew W.; Starcevic, Vladan; Salame, Wael O. (Journal of adolescent health, 2015)
Despite being relatively new, cyberbullying is now well recognized as a serious public health problem affecting children and adolescents. Scientific exploration has lagged media attention, but a synthesis of studies across several disciplines permits an understanding of its epidemiology, phenomenology, mental health dimensions, and management tools. To assess current knowledge of cyberbullying, we searched the MEDLINE, PubMed and PsycINFO databases for articles on “cyberbullying” and related designations. The Google search engine was used to capture otherwise unpublished legislative, governmental, and community response data and to help identify relevant books and book chapters. A significant proportion of children and adolescents (20%–40%) have been victims of cyberbullying, with females and sexual minorities seemingly at higher risk. Perpetrators are more likely to be male. By nature of the electronic platform, there seems to be an easier path to the bully-victim phenomenon (victims who become bullies or vice versa) than that in traditional bullying. A nonlinear relationship with age is suggested, but demographic data overall are preliminary. Accompanying psychopathology, including an increasingly well-established link to suicidality, is common. Several prevention and management approaches have been proposed to help prevent cyberbullying or mitigate its effects. Cyberbullying's seeming ubiquity, its disproportionate toll on vulnerable populations (e.g., children and sexual minorities), the link with suicidality, and the expected continued rise in Internet penetrance and connectivity make confronting it an urgent matter. A multipronged approach is most likely to succeed and would include: educational media campaigns; school-based programs; parental oversight and involvement; legislative action; and screening and evidence-based interventions by health care providers, especially pediatricians and mental health professionals. More research is needed into cyberbullying, but available data suggest a serious problem whose consequences are real and should not be dismissed as a “virtual” by-product of an increasingly digitalized childhood and adolescence.